Implementasi Security Policy Pada Firewall Di SMA Negeri 1 Una-Una - Andi Baso; Sofyan Sofyan; Musfira Musfira (Jurnal Elektronik Sistem Informasi dan Komputer, 2025)
This research is a qualitative research. This research aims to make it easier for school operators to improve the security of computer network systems. The data of this research was obtained from primary data or data on the implementation of security policies on computer networks connected to the internet and secondary data or data about the research object obtained from the SMA Negeri 1 Una-una school. Meanwhile, data analysis techniques are obtained from observations, interviews, literature, documentation. The results of this study show that this study found that one computer network connected to the internet does not have a computer network security policy. The security policy application is called Security Policy with the aim of making it easier for school operators to improve the security of computer network systems connected to the internet effectively and efficiently.